OPTIMAL CONTROL AND DIFFERENTIAL GEOMETRY APPROACHES TO HIGHWAY VERTICAL CURVE DESIGN USING ARTIFICIAL INTELLIGENCE TECHNIQUES - Балашова, Юлія; Балашов, Андрій (SWorldJournal, 2024)
The design of highway vertical curves is a complex optimization problem that must balance safety, comfort, construction cost, and environmental impact. Traditional design methods often rely on simplified models and heuristics, potentially overlooking opti